The Return of The Thaumaturge Kings: an Analysis of Presidential Discourse in Mexico and Brazil during The COVID-19 emergency in 2020 - David Ramírez Plascencia (Doxa Comunicación)
This paper analyzes the public discourse employed by presidents López Obrador in Mexico and Jair Bolsonaro in Brazil during the outbreak of the 2020 pandemic. The two cases hold important similarities: throughout the first outbreaks, both leaders had a negationist and disdained attitude towards the disease, trying to maintain their popularity by contradicting the scientific arguments about the impact of the pandemic. This article centers on Critical Discourse Analysis (CDA), the fieldwork focused on gathering information published on social media profiles and online news. Outcomes will show how the presidential public approval stood in the construction of alternative public discourse, based on fakes news, social media and political polarization that praises a messianic president with supernatural powers.